Concern for the Identity of the Priest in Light of Benedict XVI’s Teaching - Plata, Łukasz (Verbum vitae, 2025)
In the article, the author reflects on the issue of priestly identity, being experienced in a mature way, in light of the teachings of Pope Benedict XVI. Based on an analysis of the Pope’s selected statements addressed to the clergy, three fundamental, internal dimensions of priestly identity have been identified: spiritual, psychological, and intellectual. They should find expression in the priest’s external ministry as a shepherd and minister of the sacraments, a witness to the world, as well as a teacher and evangelizer. The juxtaposition of these two dimensions—internal and external—illustrates their mutual complementarity, which determines the need for their integral development. The article demonstrates the formative potential of Benedict XVI’s teaching for the renewal of priestly life in the contemporary Church.